MARKETING MIX STRATEGY IN BUILDING MSME COMPETITIVENESS IN INDONESIA - Yocky Pramudya Ananda (International Journal Labs, 2022)
Micro, small and medium enterprises are the largest group of economic actors in the Indonesian economy and have proven to be a safety valve for the national economy during a crisis and a driver of economic growth after the economic crisis. The Competition of Micro, Small and Medium Enterprises (MSMEs) follows various types of marketing strategies based on the demand of the target market. The purpose of this study is to examine the marketing mix strategy in building the competitiveness of MSMEs in Indonesia. This type of research is a case study research with a qualitative approach. Respondents in this study were SMEs in the Cirebon area. Data collection techniques using interviews, observations and documents. The data analysis technique uses research data processing with data reduction, data presentation, conclusion drawing and verification. The results of this study are that with the marketing mix strategy in building the competitiveness of MSMEs in Indonesia, MSME management seeks to determine strategies based on consumer needs. Marketing strategy to design an integrated marketing mix consisting of four Ps (product, price, place, promotion). Mix strategy has an effect on purchasing decisions and has an impact on increasing sales volume. The purpose of this strategy is to attract consumers to use the products and or services provided by MSMEs. If MSMEs are unable to maintain a marketing mix strategy, then it is likely that they will not be able to survive and even lose money. To survive, develop and be able to compete, MSMEs must be able to maintain a marketing strategy that is based on the level of consumer satisfaction